Image registration method based on mutual information about distance field of image edges - ZHANG Jian-wei; HAN Guo-qiang; WO Yan (Tongxin xuebao)
Image registration method based on mean Hausdorff distrance was simple, fast and available in application to image registration. At the same time, due to un-identical edges extracted from images, incorrect or inaccurate registration was often obtained. A new image registration method based on mutual information about distance field of image edges was presented. The distance field of the reference image edges and the binary edge image of floating image were re- garded as two discrete probability distributions, and the mutual information between them was adopted as similarity func- tion to register images. Results of experiments show that the new method is excellent to both identical and un-identical image edges.